Small-volume hypertonic saline/pentastarch improves ileal mucosal microcirculation in experimental peritonitis - Abdelnasser Assadi; Olivier Desebbe; Thomas Rimmelé; Arnal Florence; Joëlle Goudable; Dominique Chassard; Bernard Allaouchiche (MDPI AG, 2012)
We compared the effects of hypertonic saline 7.2% / 6% hydroxyethyl starch (HSS-HES) and isotonic saline 0.9% / 6% hydroxyethyl starch (ISS-HES) on ileal microcirculatory blood flow (MBF) at the initial phase of septic shock. Pigs were anesthetized and mechanically ventilated. Catheters were inserted into right atrium, pulmonary artery, carotid artery, and portal vein for hemodynamic measurements and for blood sampling. Ileal mucosal and muscularis MBF was continuously measured by laser Doppler flowmetry (LDF). Septic shock was obtained 240 min after induction of fecal peritonitis; then animals were randomized to receive 10 mL.kg-1 during 10 min of either HSS-HES or ISS-HES. Systemic and microcirculatory blood flow as well as systemic metabolism were assessed. Fecal peritonitis promoted a hypodynamic septic shock, with significant reduction of mean arterial pressure (MAP) and cardiac index (CI). Ileal mucosal MBF (-34%) and ileal muscularis MBF (-54%) significantly diminished from baseline. Contrary to ISS-HES group, mucosal MBF significantly augmented after HSS-HES (+192% at min 150 post-shock) despite low blood pressure. There was weak correlation with CI (r²= 0.2, P = 0.01) . Muscularis MBF didn't change. HSS-HES-treated animals had a significantly higher osmolarity and sodium concentration than ISS-HES group. Other variables did not change. Small-volume resuscitation with HSS-HES, but not ISS-HES, improved ileal microcirculatory impairment in experimental peritonitis model of septic shock even when MAP was low. This beneficial microcirculatory effect could be valuable in the management of early severe sepsis.